INHERITANCE PROCESS AND ITS IMPACT ON THE RELIABILITY AND DURABILITY OF USE PIPE FITTING VEHICLE POWER SYSTEMS (Municipal economy of cities (Technical science), 2013)
The results of experimental studies related to the establishment of the influence of technological heredity pretsizi ting pairs on the reliability and durability of the pipe fittings energy transportation pipeline systems.